Design and development of 2 kW, 3 dB hybrid coupler for the prototype Ion Cyclotron Resonance Frequency (ICRF) system. Issue 1 (4th October 2018) - Jain, Abhinav; Yadav, Rana Pratap; Kulkarni, S. V.
Abstract: Design and development of 2 kW, 3 dB tandem hybrid coupler for the frequency range of 155–225 MHz has been presented in this paper. The developed 3 dB coupler is to be used in a prototype of Ion Cyclotron Resonance Frequency (ICRF) system of Tokamak, which has been developed to test the resilience of ICRF network during continuously variable RF load excursions. The 3 dB coupler divides the RF power between two antennae of the prototype and protects the RF source by coupling of reflected power to the isolated port. The developed coupler shows excellent coupling flatness of −3 ± 0.3 dB over 38% of fractional bandwidth and also provides voltage standing wave ratio (VSWR) <1.3, isolation better than 32 dB and return loss better than 25 dB in full band. The presented work establishes a technique which can be useful for the development of high-power hybrid coupler in the range of high frequency (HF), very high frequency (VHF) and ultra high frequency (UHF).